THE ROLE OF POVERTY IN MEDIATING THE EFFECT OF EDUCATION AND UNEMPLOYMENT ON ECONOMIC GROWTH - Sugiarti, Rita; Astuty, Pudji (JABE (Journal of Applied Business and Economic), 2025)
The issue of poverty and economic growth is a significant problem many countries face. Many countries, including Indonesia, focus on eliminating poverty and creating good economic growth. This Research aims to test the influence of Education and Unemployment on poverty and its impact on economic growth. 34 provinces in Indonesia, with 9 years of study, resulting in 306 balanced panel data. The data were analyzed using panel data regression and influence—no direct influence on the Sobel Test. Research results show that the level of education is influential to poverty and economic growth, whereas the level of Unemployment is influential to poverty; however, it is not influential to economic growth. Poverty can also lower economic growth. Research also finds that existence influences economic growth without direct poverty. Results study. This implies that the government needs to add expenditure in the sector of Education, like help scholarships, KIP, KJP, or development infrastructure, and assistance such as BLT or social assistance, to get rid of poverty, because the second variable has proven its impact on economic growth in Indonesia.